ETHICS. (Public Management (00333611))
Highlights the online discussion of members of the International City/County Management Association, on local government management. Focus on policies that address employees' moonlighting for elected officials or for department directors and other staff members; Potential conflicts that can arise from allowing employees to work on the side for elected officials.